Feasibility and limitations of damage identification in composite materials using acoustic emission. (August 2015) - Maillet, Emmanuel; Baker, Christopher; Morscher, Gregory N.; Pujar, Vijay V.; Lemanski, Joseph R.
Abstract: One of the current challenges in health monitoring of composite materials is the use of acoustic emission to identify damage modes. Many classification procedures have been reported in the literature but none of them clearly state limitations to their applicability, making it difficult to quantify them in different testing conditions. In the present paper, a method is described to characterize energy attenuation and how it affects AE signals features based solely on AE signals recorded during mechanical tests. Limitations to damage identification based on AE signals features can therefore be defined. The method is demonstrated on AE signals recorded during tensile tests on four different layups of carbon fiber reinforced polymer composites using signals frequency centroids to describe AE sources.